Enhancing Logistics Performance through Increased Trust and Collaboration in Supply Chain Risk Management: A Focus on the Distribution Network of Manufacturing Companies - Soohyo Kim; Choyeon Kim (Systems, 2024)
This study aims to explore the significance of trust among companies within the supply chain and investigate its effect on collaborative supply chain risk management. In the current uncertain business environment, it is crucial for companies to establish trust relationships with their trading partners and collaboratively manage risks. This research seeks to understand how such trust relationships influence collaborative risk management and, subsequently, the effect of risk management collaboration on logistics performance. This study surveyed manufacturing companies in the Korean supply chain, and data were analyzed using SPSS 23.0 and AMOS 23.0. The results of this study imply that cognitive trust, related to the partner’s expertise and capabilities, is more crucial than emotion-based affective trust in fostering collaborative supply chain risk management among companies within the supply chain, especially in the current unpredictable and complex business environments. Given the supply chain disruptions caused by uncertainties in the business environment, it is imperative to effectively manage risks and restructure the disrupted supply chain. Therefore, companies need to strive to demonstrate their expertise and capabilities to build cognitive trust and enhance logistics performance through supply chain risk management collaboration.